Diabolical possession and the case behind "The Exorcist": an overview of scientific research with interviews with witnesses and experts - Rueda, Sergio A. (McFarland & Company, Inc., Publishers, 2018)
"Reexamining the purported 1949 exorcism of a 13-year old boy in Mount Ranier, Maryland the author explores the subject of demonic possession in the light of science. Eyewitness accounts, unpublished photos and never before seen documents from the archives of Rhine Research Foundation provide fresh perspective on events that inspired the novel, and later the film, The Exorcist"